miR-191-5p suppresses PRRSV replication by targeting porcine EGFR to enhance interferon signaling - Pan, Yu; Zhang, Lin; Ma, Wenjie; Ibrahim, Yassein M.; Zhang, Wenli; Wang, Mengjie; Wang, Xinrong; Xu, Yunfei; Gao, Caixia; Chen, Hongyan; Zhang, He; Xia, Changyou; et al. (Frontiers in Microbiology, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a major thread to the global swine industry, lack of effective control strategies. This study explores the regulatory role of a small non-coding RNA, miR-191-5p, in PRRSV infection. We observed that miR-191-5p significantly inhibits PRRSV in porcine alveolar macrophages (PAMs), contrasting with negligible effects in MARC-145 and HEK293-CD163 cells, suggesting a cell-specific antiviral effect. Further investigation unveiled that miR-191-5p directly targets the porcine epidermal growth factor receptor (EGFR), whose overexpression or EGF-induced activation suppresses type I interferon (IFN-I) signaling, promoting PRRSV replication. In contrast, siRNA-or miR-191-5p-induced EGFR downregulation or EGFR inhibitor boosts IFN-I signaling, reducing viral replication. Notably, this miRNA alleviates the suppressive effect of EGF on IFN-I signaling, underscoring its regulatory function. Further investigation revealed interconnections among miR-191-5p, EGFR and signal transducer and activator of transcription 3 (STAT3). Modulation of STAT3 activity influenced IFN-I signaling and PRRSV replication, with STAT3 knockdown countering EGFR activation-induced virus replication. Combination inhibition of STAT3 and miR-191-5p suggests that STAT3 acts downstream in EGFR's antiviral response. Furthermore, miR-191-5p's broad efficacy in restricting various PRRSV strains in PAMs was identified. Collectively, these findings elucidate a novel mechanism of miR-191-5p in activating host IFN-I signaling to inhibit PRRSV replication, highlighting its potential in therapeutic applications against PRRSV.